Utilization, Satisfaction and Out-Of-Pocket Expenditure Associated with National Health Insurance Scheme among Patients Attending Lumbini Medical College - Marhatta, Anu; Nepal, Samata; Shrestha, Sajja (Nepal Medical College Journal, 2025)
Health insurance is a method to finance healthcare with coverage that pays off medical expenses that arise due to an illness, injury or accidents. The National Health Insurance Scheme was introduced by the Government of Nepal in April 2016. Initially roll-out in three districts, social health insurance has been gradually expanded and is now available in all 77 districts of Nepal. The government of Nepal aims to provide quality health care services without imposing a financial burden on its citizens through the health insurance policy scheme. The study intends to assess utilization, and satisfaction of the national health insurance scheme among patients visiting Lumbini medical college teaching hospital. This is a cross-sectional analytical study done in 411 patients visiting Lumbini Medical College Teaching Hospital, Palpa using simple random sampling method. The selected patients were interviewed regarding socio-demographic details, utilization status and satisfaction level of the NHIS using a pre-structured questionnaire with a face-to-face patient exit interview technique. Data was entered in SPSS-16 for analysis. The data was presented in frequency, percentage, and, figures to express the results. The NHIS was utilized by 88.3% of insured respondents and 46.8% of insured spend above the optimum amount of insurance to cover all their health expenditures. Satisfaction with the NHIS was reported by 66.6% of the participants. The study revealed that majority of patients are utilizing NHIS with satisfaction.